THE ROLE OF FUN MATH ADVENTURE MEDIA IN DEVELOPING EARLY CHILDHOOD NUMERACY AND PROBLEM-SOLVING SKILLS - Pristiwati, Lila; Fitri, Ruqoyyah; Setyawati, Sri; Istiq’faroh, Nurul; Kristanto, Andi; Syahidul Haq, Mohammad (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2026)
This study aims to describe the role of the Fun Math Adventure media in developing early childhood numeracy and problem-solving skills through a phenomenological qualitative approach. Data were collected through participatory observations, in-depth interviews, and documentation, and were analyzed using the interactive model of Miles and Huberman. The credibility of the data was strengthened through technique triangulation and member checking with teachers to ensure the consistency and accuracy of the findings. The results indicate that Fun Math Adventure enhances children’s focus, persistence, and engagement in numeracy activities, while also encouraging the emergence of independent problem-solving strategies. The digital environment further enriches social interactions by facilitating collaborative discussions and shared exploration among children. In addition, the use of this media provides teachers with opportunities to design more adaptive, varied, and child-centered learning experiences. The study contributes new insights into the effective integration of play-based learning and digital media in early childhood education, and offers practical implications for teachers implementing the Merdeka Curriculum.